MPLEMENTASI MANAJEMEN MUTU PROGRAM PEMBELAJARAN DI MADRASAH IBTIDAIYAH (MI) AL-AZHAR BANDUNG TULUNGAGUNG - Fitri, Agus Zaenul (Dinamika, 2013)
ABTRACTÂ The Islamic Elementary School (MI) Al Azhar is one of private islamic elementary school that has central of excellence-oriented in implementing quality of learning program.Â  In this program, it doesnât only develop the students intelligence but also develop emotional aspect, social aspect, and spiritual aspect.Â  In this study, there are research finding; 1) Policy in planning. 2) Teachers management oriented in competence and professional achievement. 3) Students management. 4) Learning management. 5) Method Management. 6) Learning resources management. 7) Media management. 8) Internal-external environment management. 9) Evaluation supervision.Â Kata Kunci: Manajemen, Mutu, Program, Pembelajaran.